Drawing Analogies between Logic Programming and Natural Language Argumentation Texts to Scaffold Learners’ Understanding - Ragonis, Noa; Shilo, Gila (Journal of information technology education, 2014)
The paper presents a theoretical investigational study of the potential advantages that secondary school learners may gain from learning two different subjects, namely, logic programming within computer science studies and argumentation texts within linguistics studies. The study suggests drawing an analogy between the two subjects since they both require similar abstraction skills manifested in the analysis of texts and in capturing their logic structure and inference. We propose that drawing analogies between two representations of argumentation texts can advance students' understanding, and, furthermore, using computerized systems may enable students to interact with linguistics texts and thus enhance their understanding. The paper explores the connections between the two disciplines, emphasizing the similar structures used to express the knowledge, and presents the similar abstract thinking processes that learners must carry out. Further implications for curricula are discussed.